The Role of Market Orientation and Product Quality on Competitive Advantage in Micro, Small and Medium Enterprises in Batam City - Hendri Herman; Suyono Suyono (Universitas Putera Batam, 2023)
Small and Medium Enterprises certainly want their businesses to make a profit so that business actors can continue to run their business activities. The success of a business is certainly inseparable from the Competitive Advantage possessed by the business. Small and medium enterprises certainly have a major contribution to the rolling of the wheels of a country's economy, not only because small and medium enterprises are seeds that enable the growth of large businesses, but also because small and medium enterprises provide certain services for the community which for large businesses are considered less efficient in cost. The object of this research is Small and Medium Enterprises located in the city of Batam. Data collection techniques in this study are using the help of questionnaire distribution, conducting direct interviews with small and medium enterprises as respondents. The results of the study stated that market orientation has a significant effect on competitive advantage, product quality has a significant effect on competitive advantage, market orientation and product quality simultaneously have a significant effect on competitive advantage